2021
DOI: 10.1111/jan.15102
|View full text |Cite
|
Sign up to set email alerts
|

An integrative review of Indigenous informal caregiving in the context of dementia care

Abstract: Aims To appraise the empirical literature on the needs of Indigenous informal caregivers caring for people living with dementia in Indigenous communities. Design Whittemore and Knafl's updated approach to integrative reviews, PRISMA guidelines, and CASP checklists for narrative analysis were followed. Data sources A systematic search of published empirical literature from January 2010 to August 2020 was undertaken in six databases. Review methods Fifty‐one studies met the research question and the inclusion cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 91 publications
1
8
0
1
Order By: Relevance
“…Furthermore, if individuals continue to lack representation in Alzheimer's research, they will not receive the benefits of racially and ethnically sensitive prevention, treatment or care innovations 425,427 . Establishing stronger relationships with existing organizations and resources in Black communities, indigenous communities and other communities of color offers the potential for research‐based partnerships to enhance representation in Alzheimer's disease research and result in more culturally appropriate and effective services 432,434,438–449 …”
Section: Caregivingmentioning
confidence: 99%
“…Furthermore, if individuals continue to lack representation in Alzheimer's research, they will not receive the benefits of racially and ethnically sensitive prevention, treatment or care innovations 425,427 . Establishing stronger relationships with existing organizations and resources in Black communities, indigenous communities and other communities of color offers the potential for research‐based partnerships to enhance representation in Alzheimer's disease research and result in more culturally appropriate and effective services 432,434,438–449 …”
Section: Caregivingmentioning
confidence: 99%
“…Canadian FCGs provide 90% of the care to people living in private community homes [ 31 ] and assist with 15 to 30% of the care in supportive living and long-term care [ 32 , 33 ]. Many of the participants in this study suggested that First Nations FCGs are likely providing more care, as they expected to provide care without the support available to nonindigenous Canadian caregivers [ 16 ]. Indigenous FCGs urgently need integrated policy, health, and social care systems to support them to care for and maintain their health.…”
Section: Discussionmentioning
confidence: 99%
“…They too were stymied by the complicated records systems and policies between different government levels. Racine and colleagues’ [ 16 ] review of the experience of indigenous caregiving for dementia related to the burden of geographic isolation, lack of funding for healthcare facilities, and legacies of colonial policies and trauma. We agree that these factors also increase the indigenous structural burden of care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations